The mechanism of mTOR (mammalian target of rapamycin) in a mouse model of polycystic ovary syndrome (PCOS) - Yaba Aylin; Demir Necdet (Journal of Ovarian Research, 2012)
Abstract Polycystic ovary syndrome (PCOS) is a common and complex endocrine disorder affecting 5-10% of women in reproductive age that is characterized by hyperandrogenism, oligo- or anovulation and infertility. However the pathophysiology of PCOS still remains unknown. The mammalian target of rapamycin (mTOR) is a central component that regulates various processes including cell growth, proliferation, metabolism, and angiogenesis. mTOR signaling cascade has recently been examined in ovarian follicles where it regulates granulosa cell proliferation and differentiation. mTOR functions as two complexes, mTOR complex 1 and 2. Therefore, we hypothesized that mTORC1 and/or 2 may have important role in proliferation of theca and granulosa cells in PCOS. In the present study, we sought to determine the mTOR signaling pathway in PCOS mouse ovary. We designed 3 groups: Control (C, no treatment), PCOS (P, The injection of DHEA (6 mg/100 g BW in 0.1 ml of sesame oil) (s.c) for 20 consecutive days), Vehicle (V, daily (s.c) sesame oil alone injection). Our results showed that mTORC1 and mTORC2-mediated signaling may play a role in PCOS mouse ovary. These findings provide evidence that mTORC1 and mTORC2 may have responsibility in increased ovarian follicular cell proliferation and growth in PCOS. Consequently, these results suggest that the mTOR signaling pathways (mTORC1 and mTORC 2) may create new clinical strategies to optimize developmental competence of PCOS should target correction of the entire follicle growth, oocyte development process and anovulatory infertility in PCOS.